The effects of valence and arousal on time perception in individuals with social anxiety - Yoo, Jung-Yi; Lee, Jang-Han (Frontiers in Psychology, 2015)
Time distortion in individuals with social anxiety is demonstrated as the seemingly slower passage of time in a social situation. Time distortion in individuals relates not only to the arousal, but also to valence. Consequently, adaptive behavior is disrupted and interpersonal situations are avoided. We explored the effect of valence and arousal on time distortion in individuals with social anxiety. Participants were assigned to 2 groups, High Anxiety (HA) and Low Anxiety (LA); and presented with 4 types of facial expression stimuli (positive-high arousal, positive-low arousal, negative-high arousal, and negative-low arousal) to estimate the duration of stimulus. Results indicated that the HA group perceived longer in negative-high arousal than other stimuli, but the LA group perceived longer positive-low arousal stimuli than others. These results suggested that anxious individuals’ time distortion becomes more severe in situations that evoke high arousal accompanied by negative emotion.